Variações sazonais nas composições química e isotópica das águas superficiais na Bacia do Rio Jacaré-Pepira/SP - Farinha, Bárbara Saeta [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In a watershed, the surface flow in the river channel is the sum of the contribution of groundwater (base flow) and surface flow (run-off), each one contributing in different proportions throughout the year. The use of isotopic and chemical tracers to quantify these contributions in watersheds of various scales is a widely used tool worldwide, but much less used in Brazil. Seasonal variations of the chemical and isotopic compositions of surface water in two small catchments in the Alligator-Pepira River watershed in the city of Brotas (SP) were evaluated, in order to determine the contribution of each of these components in surface flow. Monthly samples of surface water and rainfall were collected between the months of December / 2014 and November / 2015. Rainfall had poor isotopic composition during the rainy season (Dec / 2014 to April / 2015) and higher values for the remainder of the period, without recognizing the effect of the quantity on these values. During the period, the electrical conductivity of surface water showed values of 16,25S cm -¹ for point 1, and 78.09S cm -¹ for point 2, reflecting different degrees of mineralization, associated with differences in the geological substratum of the watershed. Surface waters were classified as bicarbonate sodium-calcic in point 1 and bicarbonate calcic in 2. During the monitoring period there was a negative correlation between precipitation and nitrate concentrations measured in surface waters, indicating that the major contributions of this compound are associated to the discharge of the groundwater. The observed variations in the isotopic composition of precipitation are reflected in the surface water, with surface waters having higher variations in isotopic composition during rainy periods. Also, both points presented similar and stable isotopic compositions during the dry season, indicating the discharge contribution of groundwater flow in maintaining the channels...

Em uma bacia hidrográfica o fluxo superficial no canal do rio representa a soma da contribuição das águas subterrâneas (fluxo de base) e do fluxo superficial (run-off), que contribuem em proporções variáveis ao longo do ano. A utilização de traçadores isotópicos e químicos para a quantificação dessas contribuições em bacias hidrográficas de diversas escalas é ferramenta bastante utilizada mundialmente, entretanto, pouco aplicada em território brasileiro. Nesse sentido foram avaliadas as variações sazonais das composições químicas e isotópicas das águas superficiais em duas pequenas bacias hidrográficas na Bacia do Rio Jacaré-Pepira, na cidade de Brotas (SP), com o objetivo de se averiguar a contribuição de cada uma dessas componentes no fluxo superficial. Foram coletadas amostras mensais, entre os meses de dezembro/2014 e novembro/2015, das águas superficiais e da precipitação. A precipitação apresentou composição isotópica empobrecida durante a estação chuvosa (dez/2014-abril/2015) e valores mais enriquecidos durante o restante do período, entretanto, sem ser reconhecido o efeito quantidade sobre esses valores. No período, a condutividade elétrica das águas superficiais apresentou valores médios de 16,25S cm -¹ para o ponto 1, e de 78,09 S cm -¹ no ponto 2, refletindo diferentes graus de mineralização, associados as diferenças no substrato geológico das bacias. As águas superficiais foram classificadas como Bicarbonatadas Calcio-Sódicas no ponto 1 e Bicarbonatadas Calcicas no ponto 2. Ao longo do período de monitoramento observou-se correlação negativa entre a precipitação e as concentrações de nitrato medidas nas águas superficiais, indicando que as maiores contribuições desse composto estão associadas à descarga das águas subterrâneas. As variações observadas na composição isotópica da precipitação refletem-se nas águas superficiais, nos períodos mais chuvosos...
Keywords: Hidrogeologia; Águas subterrâneas; Águas superficiais; Bacias hidrograficas; Chuvas; Nitratos; Geoquimica; Aquífero Guarani; Jacare Pepira, Rio (SP)